Planetary influence on the young Sun's evolution: the solar neutrino probe - Lopes, Ilidio (2014)
Recent observations of solar twin stars with planetary systems, like the Sun, have uncovered that these present a peculiar surface chemical composition. This is believed to be related to the formation of earth-like planets. This suggests that twin stars have a radiative interior that is richer in heavy elements than their envelopes. Moreover, the current standard solar model does not fully agree with the helioseismology data and solar neutrino flux measurements. In this work, we find that this agreement can improve if the Sun has mass-loss during the pre-main sequence, as was previously shown by other groups. Despite this better agreement, the internal composition of the Sun is still uncertain, especially for elements heavier than helium. With the goal of inferring the chemical abundance of the solar interior, we tested several chemical compositions. We found that heavy element abundances influence the sound speed and solar neutrinos equally. Nevertheless, the carbon-nitrogen-oxygen (CNO; 13N, 15O and 17F) neutrino fluxes are the most affected; this is due to the fact that contrarily to proton-proton (pp, pep, 8B and 7Be) neutrino fluxes, the CNO neutrino fluxes are less dependent on the total luminosity of the star. Furthermore, if the central solar metallicity increases by 30 per cent, as hinted by the solar twin stars observations, this new solar model predicts that 13N, 15O and 17F neutrino fluxes increase by 25-80 per cent relative to the standard solar model. Finally, we highlight that the next generation of solar neutrino experiments will not only put constraints on the abundances of carbon, oxygen and nitrogen, but will also give some information about their radial distribution.